1993
DOI: 10.1016/0014-5793(93)80528-3
|View full text |Cite
|
Sign up to set email alerts
|

5‐lipoxygenase‐activating protein is an arachidonate binding protein

Abstract: 5-Lipoxygenase-activating protein (FLAP) is an 1 S-kDa integral membrane protein which is essential for cellular leukotriene (LT) synthesis, and is the target of LT biosynthesis inhibitors. However, the mechanism by which FLAP activates S-LO has not been determined. We have expressed high levels of human FLAP in Spodopteru frugiperda (39) insect cells infected with recombinant baculovirus, and used this system to demonstrate that FLAP specifically binds ['2sI]L-739,059, a novel photoaffinity analog of arachido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(133 citation statements)
references
References 20 publications
7
125
0
1
Order By: Relevance
“…FLAP is an AA binding protein that stimulates the utilization of AA by 5-LO and also augments 5-LO membrane association. By affecting the ratio of 5-LO products (5-HETE/LTA 4 ), FLAP increases the efficiency of LTA 4 synthesis (23)(24)(25). Indeed, we could show that the FLAP inhibitor MK-886 was able to impair LXA 4 and RvD 1 biosynthesis in precursortreated PMNLs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…FLAP is an AA binding protein that stimulates the utilization of AA by 5-LO and also augments 5-LO membrane association. By affecting the ratio of 5-LO products (5-HETE/LTA 4 ), FLAP increases the efficiency of LTA 4 synthesis (23)(24)(25). Indeed, we could show that the FLAP inhibitor MK-886 was able to impair LXA 4 and RvD 1 biosynthesis in precursortreated PMNLs.…”
Section: Discussionmentioning
confidence: 78%
“…In LT biosynthesis, FLAP is thought to transfer liberated AA to activated 5-LO (23)(24)(25). In addition, it also fosters the membrane association of 5-LO (26).…”
Section: Resultsmentioning
confidence: 99%
“…Conversion of AA to 5-HPETE followed a function of AA availability while the transformation of 5-HPETE to LTA 4 followed a bell-shaped curve, indicating that the second enzymatic reaction catalyzed by 5-LO, but not the first, is affected at higher AA concentrations. Although the explanation for this inhibition is not clear, high concentrations of AA were previously reported to bind to FLAP [46] and to inhibit LT biosynthesis [38]. Also, in a recent study where 5-lipoxygenase-activating protein (FLAP) was shown to be present in neutrophil membranes as monomers and homodimers, and where the functional importance of the dimer (over the monomer) in LT biosynthesis was highlighted [47], it was observed that high AA concentrations decreased FLAP dimer levels, supporting the possibility that high concentrations of AA could disrupt or destabilize the FLAP dimer, an effect which correlates with the suppression of 5-LO product biosynthesis by the fatty acid.…”
Section: Discussionmentioning
confidence: 96%
“…In the first steps of LT biosynthesis, AA liberated by the action of phospholipase A 2 (PLA 2 ), in particular cytosolic PLA 2 (cPLA 2 ), is transferred to 5-LO by 5-LOactivating protein (FLAP) (6,7). Upon activation, 5-LO translocates to the nuclear envelope, in which FLAP is localized (8,9).…”
mentioning
confidence: 99%